LEAN CONSTRUCTION, WHERE INNOVATION MEETS EXCELLENCE, TRANSFORMING CONSTRUCTION CULTURE FOR SUCCESS - Er. Dipanjan Dutta; Er. Aritra Roy; Er. Girish Bonde; Prof. Raju Narwade; Dr. Sparsh Johari (IJRDO - Journal of Mechanical And Civil Engineering, 2025)
The Indian Lean Construction sector has experienced substantial growth and development in recent years, owing to the adoption of lean concepts and techniques, however, lean construction practices have been underutilized by Indian construction firms. The paper aims to investigate the role of lean construction tools in identifying and addressing wastages in the construction industry. Lean construction principles and methodologies have gained prominence as an effective means to improve project efficiency, reduce costs, and enhance overall productivity. The focus area of the paper is to explore how specific lean construction tools can help identify various forms of waste commonly found in construction processes. A systematic approach was adopted to analyze workflow data using three key lean construction tools viz. the Last Planner System (LPS), 5S methodology, and Work Sampling. These tools were selected due to their ability to provide insights into different aspects of construction wastages. The findings indicated that lean construction tools play a significant role in waste identification within the construction industry. The implementation of the lean tool provided valuable data and visual representations that enabled project teams to identify and address various types of waste, including material waste, excess inventory, unnecessary motion, waiting time, and inefficient processes. By deploying lean construction tools, it was observed that it can lead to substantial improvements in productivity, cost reduction, and project performance. By identifying and eliminating wastages, construction companies can streamline processes, enhance resource utilization, and improve overall project outcomes. The research outcomes help to derive insights for lean enthusiasts trying to adopt lean principles and tools to optimize construction processes and drive continuous improvement